PENYUSUNAN TUGAS DAN TANGGUNGJAWAB KARYAWAN PADA UNIVERSITAS X - Eny Rohyati (Jurnal Psikologi, 2016)
Objective of this research is to verivy that having undetailed job description will give impact on low work effectiveness. Five empoyees participated in this research. They were taken purposively since they had problem when working in a team, and therefore their work effectiveness were low. They had less understanding on their detailed job description. Observation, interview, and documentation research methods were used in order to collect the data. This research revealed that those employees had low understanding on their duty and responsibility. Indeed, this research should warn the top leader to monitor and evaluate their employees regularly, including the middle leader. Work monitoring and work evaluation should also checked all employee’s understanding on their job description.